Palatal Lift Prosthesis for Velopharyngeal Incompetence: A Case Report - Mirna Garhnayak1 , Lokanath Garhnayak2 , Kajal Kiran Sahoo3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Velopharyngeal incompetence often distorts the voice quality making it difficult for the listener to comprehend.A cost-effective treatment approach for this is palatal lift prosthesis. This prosthesis enables the incompetentsoft palate to approximate with the posterior pharyngeal wall. As a result articulation of speech is improved